Does the World Bank Foster Business? - Giordano, Raffaela; Pagano, Patrizio (World Bank, Washington, DC, 2017)
This study investigates the impact of World Bank development policy loans on the ease of doing business. It finds that the cumulative number of development policy loans enhances business climate, especially for less developed countries and when combined with an International Monetary Fund assistance program. The results are robust to several specifications and sample restrictions, and controlling for possible endogeneity. When the cumulative number of loans and their cumulative value are included in the regression, the value is no longer significant. This finding suggests that overall engagement with the World Bank is more relevant than the amount of resources invested in the project.